Histopathological dimensions differ between aganglionic and ganglionic bowel wall in children with Hirschsprung’s disease - Christina Graneli; Sofia Patarroyo; Rodrigo Munoz Mitev; David Gisselsson; Emilia Gottberg; Tobias Erlöv; Tomas Jansson; Kristine Hagelsteen; Magnus Cinthio; Pernilla Stenström (BMC Pediatrics, 2022)
Highlights • To confirm ganglionic bowel wall in Hirschsprung’s disease, intra-operative frozen biopsy samples are required. This means a prolonged anesthesia time and a more immediate diagnostic method is warranted. • Muscle layers’ thicknesses differ between aganglionic and ganglionic bowel walls in children with Hirshsprung’s disease. These findings could be transferred to instant imaging techniques. • See the attached Supplementary Figure 2